Classical methods of Chemical stability: Comparison of analyses for gunpowders - Rakić Magdalena; Krstović Mirjana; Dimić Mirjana; Fidanovski Bojana (Scientific Technical Review, 2021)
The main ingredient of gunpowder is nitrocellulose. For slowing down the catalytical decomposition process, predominated stabilizer diphenylamine is in use for single-base gunpowder, as well as for propellants. On the other hand, the stabilizer wears out over time, which causes changes in chemical stability of energetic materials. One of the classical methods for determination the chemical stability is the Bergman-Jung method, which has two subgroups. This paper presents comparative analyses for twelve NC and five NCD gunpowder. Namely, both subgroups are based on the calculation of the volume of nitric oxide gases, but the difference between them depend on the method of collecting and determining released gases.